2014
DOI: 10.1016/j.jvs.2013.10.054
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary outcomes of endovascular interventions for acute limb ischemia

Abstract: Endovascular therapy with thrombolysis using tissue plasminogen activator remains an effective treatment option for patients presenting with mild or moderate lower extremity ALI, with equal benefit derived with CDT or PMT. Patients with end-stage renal disease or poor pedal outflow have an increased risk of limb loss and may benefit from alternative revascularization strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
81
3
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 11 publications
10
81
3
5
Order By: Relevance
“…In this comprehensive multicenter registry, we found a technical failure rate of 11% among ALI patients treated with PVI, which is comparable to those previously reported 18, 20, 21. One study found a technical failure rate of 1.6%,19 but this lower rate may reflect the difference in endovascular treatment techniques used.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In this comprehensive multicenter registry, we found a technical failure rate of 11% among ALI patients treated with PVI, which is comparable to those previously reported 18, 20, 21. One study found a technical failure rate of 1.6%,19 but this lower rate may reflect the difference in endovascular treatment techniques used.…”
Section: Discussionsupporting
confidence: 86%
“…Our in‐hospital and 1‐year mortality of 4% and 15% were comparable to 3% to 4% and 14.3% to 18% presented from these single‐center studies 18, 19, 20, 21, 22. Interestingly, our 6% major amputation rate at 1 year after PVI was significantly lower than the rates of 13% to 32% as previously reported 18, 20, 21, 22. This may be because of the heterogeneity in patient selection and Rutherford class severity among the studies.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations